2016
DOI: 10.3389/fgene.2016.00030
|View full text |Cite
|
Sign up to set email alerts
|

Use of Genomic Tools to Improve Cattle Health in the Context of Infectious Diseases

Abstract: Although infectious diseases impose a heavy economic burden on the cattle industry, the etiology of many disorders that affect livestock is not fully elucidated, and effective countermeasures are often lacking. The main tools available until now have been vaccines, antibiotics and antiparasitic drugs. Although these have been very successful in some cases, the appearance of parasite and microbial resistance to these treatments is a cause of concern. Next-generation sequencing provides important opportunities t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 172 publications
(164 reference statements)
2
18
0
Order By: Relevance
“…In general, this is consistent with the conclusion of several authors that each infectious agent specifically interacts with the host's immune system, and for such pathogens these mechanisms often do not overlap [40].…”
Section: Erythrocyte and Leukocyte Profiles Of Peripheral Blood In Blsupporting
confidence: 91%
“…In general, this is consistent with the conclusion of several authors that each infectious agent specifically interacts with the host's immune system, and for such pathogens these mechanisms often do not overlap [40].…”
Section: Erythrocyte and Leukocyte Profiles Of Peripheral Blood In Blsupporting
confidence: 91%
“…This is clearly motivated by the fact that infections cause a major economic burden in the cattle industry worldwide. In this context, GWASs and other genomic approaches are regarded as powerful strategies to develop breeding programs aimed at the generation of less susceptible livestock (Raszek et al, 2016).…”
Section: Gwass In Cattle and Swinementioning
confidence: 99%
“…Likewise, GWASs for susceptibility to bovine tuberculosis (caused by Mycobacterium bovis) yielded inconsistent results (Bermingham et al, 2014;Finlay et al, 2012;Kassahun et al, 2015;Richardson et al, 2016). Efforts to identify susceptibility alleles for other infectious diseases detected small-effect loci with poor replicability (reviewed in (Raszek et al, 2016)). To date, the greatest success was obtained for mastitis, which is commonly caused by bacterial infections; regions spanning the DCK, SLC4A4, and EDN3 genes were detected in at least two studies (Kanazawa et al, 1989;Sahana et al, 2013;Sodeland et al, 2011;Wu et al, 2015).…”
Section: Gwass In Cattle and Swinementioning
confidence: 99%
“…Rios et al (2016) reported that viable alternatives to antibiotics might be bacteriophage therapy, lysin therapy, antimicrobial peptides (amphiphilic polypeptides), and bacteriocins. Genomic tools derived from next generation sequencing will allow for a better definition of pathogen profile, the evolution of the gene-resistance mutation, and the focus on host-pathogen interaction to enhance beneficial effects of the microbiome (Raszek et al, 2016).…”
Section: Antibiotics Use and Antimicrobial Resistancementioning
confidence: 99%